2020
DOI: 10.1093/cid/ciaa1901
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Previously Healthy Cryptococcal Meningoencephalitis Patients Treated With Pulse Taper Corticosteroids for Post-infectious Inflammatory Syndrome

Abstract: Background Cryptococcal meningoencephalitis (CM) is a major cause of mortality in immunosuppressed patients and previously healthy individuals. In the latter, a post-infectious inflammatory response syndrome (PIIRS) is associated with poor clinical response despite antifungal therapy and negative CSF cultures. Data on effective treatment are limited. Methods Between March 2015 and March 2020, 15 consecutive previously healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…The clinical relevance of this finding remains unclear, as, at the time of the study, we were lacking comprehensive data regarding COVID-related symptoms or COVID-suspected symptoms among newborns, repeated testing and long-term follow-up. Perinatal transmission of SARS-CoV-2 has been reported by others, both in case of vaginal and cesarean sections, and was associated in some cases with neonatal symptoms 1 , 4 , 22 . In all reported cases, the possibility of postnatal infection through contacts with parents or medical personal remains difficult to exclude 1 , 4 .…”
Section: Discussionmentioning
confidence: 62%
“…The clinical relevance of this finding remains unclear, as, at the time of the study, we were lacking comprehensive data regarding COVID-related symptoms or COVID-suspected symptoms among newborns, repeated testing and long-term follow-up. Perinatal transmission of SARS-CoV-2 has been reported by others, both in case of vaginal and cesarean sections, and was associated in some cases with neonatal symptoms 1 , 4 , 22 . In all reported cases, the possibility of postnatal infection through contacts with parents or medical personal remains difficult to exclude 1 , 4 .…”
Section: Discussionmentioning
confidence: 62%
“…This altered balance results in an excessive host immune response to infection within the space-confines of the skull, causing significant pathology (32), even in the presence of reduced CD40L signaling, as suggested by the present case. During PIIRS an appropriate pro-inflammatory cytokine response including interferon (IFN)-g and interleukin (IL)-6 stimulates T helper cells to cause immune cells immune mediated host damage but with an alternately activated macrophage subtype (M2) that is less effective at clearing nonviable fungal debris (33,34). This paradoxical immune response has been studied by Panackal et al analyzing the soluble and cellular responses to Cryptococcus in both blood and CSF in a consecutive cohort of non-HIV, nontransplant individuals with no comorbidities or iatrogenic immunosuppression who developed severe central nervous system disease (s-CNS) (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, after fungicidal therapy by agents such as amphotericin B, rupture of the fungus releases internal proteins and exposes cell wall antigens that provide additional antigenic targets recognizable by the immune-deficient host without a need for immune reconstitution as in HIV-related IRIS (24). Indeed, in a previous report (33), patients with idiopathic CD4 lymphopenia and autoantibodies to granulocyte-monocytic colony stimulating factor (anti-GMCSF), well recognized risk factors for cryptococcal disease (3) developed PIIRS after therapy as in the present case that was also responsive to corticosteroids. Thus, this case extends the spectrum of patients described with PIIRS and the generalizability of this adjuctive therapy in PIIRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the antibody response may be associated with disease severity, and it has been reported that patients with mild infections may not develop detectable amounts of neutralizing antibodies 3 , 4 , 9 . However, the exact nature of seroconversion with respect to patient risk factors and disease severity is still controversial 4 , 6 , 7 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%